An improved in vivo deuterium labeling method for measuring the biosynthetic rate of cytokinins - Tarkowski, Petr; Floková, Kristýna; Václavíková, Kateřina; Jaworek, Pavel; Raus, Martin; Nordström, Anders; Novák, Ondřej; Doležal, Karel; Sebela, Marek; Frébortová, Jitka (Molecules (Basel, Switzerland), 2010)
An improved method for determining the relative biosynthetic rate of isoprenoid cytokinins has been developed. A set of 11 relevant isoprenoid cytokinins, including zeatin isomers, was separated by ultra performance liquid chromatography in less than 6 min. The iP-type cytokinins were observed to give rise to a previously-unknown fragment at m/z 69; we suggest that the diagnostic (204-69) transition can be used to monitor the biosynthetic rate of isopentenyladenine. Furthermore, we found that by treating the cytokinin nucleotides with alkaline phosphatase prior to analysis, the sensitivity of the detection process could be increased. In addition, derivatization (propionylation) improved the ESI-MS response by increasing the analytes' hydrophobicity. Indeed, the ESI-MS response of propionylated isopentenyladenosine was about 34% higher than that of its underivatized counterpart. Moreover, the response of the derivatized zeatin ribosides was about 75% higher than that of underivatized zeatin ribosides. Finally, we created a web-based calculator (IZOTOP) that facilitates MS/MS data processing and offer it freely to the research community.
Keywords: Internet; Isotope Labeling; Deuterium; cytokininy; software; internet; deuterium; izotopové značení; Software; Arabidopsis; Cytokinins